Genomic Approaches for Conservation Management in Australia under Climate Change - Onley, Isabelle R. (Life (Basel), 2021)
Conservation genetics has informed threatened species management for several decades. With the advent of advanced DNA sequencing technologies in recent years, it is now possible to monitor and manage threatened populations with even greater precision. Climate change presents a number of threats and challenges, but new genomics data and analytical approaches provide opportunities to identify critical evolutionary processes of relevance to genetic management under climate change. Here, we discuss the applications of such approaches for threatened species management in Australia in the context of climate change, identifying methods of facilitating viability and resilience in the face of extreme environmental stress. Using genomic approaches, conservation management practices such as translocation, targeted gene flow, and gene-editing can now be performed with the express intention of facilitating adaptation to current and projected climate change scenarios in vulnerable species, thus reducing extinction risk and ensuring the protection of our unique biodiversity for future generations. We discuss the current barriers to implementing conservation genomic projects and the efforts being made to overcome them, including communication between researchers and managers to improve the relevance and applicability of genomic studies. We present novel approaches for facilitating adaptive capacity and accelerating natural selection in species to encourage resilience in the face of climate change.